1974
DOI: 10.1002/ijc.2910140604
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies on human lymphoblastoid cell lines from burkitt's lymphomas and other sources

Abstract: The occurrence and incidence of a characteristic banding abnormality in a No. 14 chromosome has been studied in Burkitt-lymphoma-derived and certain other EB virus-associated lymphoblastoid cell lines. The abnormality was readily detected in 7 out of 7 Burkitt lines, and when present could be seen in 100% of cells with recognizable No. 14 chromosomes. In contrast, the abnormality was not observed in 775 cells from 31 infectious mononucleosis-derived lines nor in 450 cells from 18 lines obtained from cord blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

1977
1977
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 16 publications
3
30
0
4
Order By: Relevance
“…14 chromosome of Burkitt lymphoma cells in biopsy samples and after culture (Manolov & Manolova, 1972) seems to be unrelated to EB virus, since it has been shown to be lacking in EB virus-carrying lymphoid cells from other sources (Jarvis et al, 1974;Zech et al, 1976). This concept has been confirmed by studies of somatic cell hybrids made between mouse cells and EB virus-carrying human lymphoid cells, which have shown that after the preferential loss of some human chromosomes expression of the EB virus nuclear antigen (EBNA) (Reedman and Klein, 1]973) was lost despite the continuing presence of the human D14 chromosome, indicating that the viral genome was not associated with this particular chromosome (Glaser et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 chromosome of Burkitt lymphoma cells in biopsy samples and after culture (Manolov & Manolova, 1972) seems to be unrelated to EB virus, since it has been shown to be lacking in EB virus-carrying lymphoid cells from other sources (Jarvis et al, 1974;Zech et al, 1976). This concept has been confirmed by studies of somatic cell hybrids made between mouse cells and EB virus-carrying human lymphoid cells, which have shown that after the preferential loss of some human chromosomes expression of the EB virus nuclear antigen (EBNA) (Reedman and Klein, 1]973) was lost despite the continuing presence of the human D14 chromosome, indicating that the viral genome was not associated with this particular chromosome (Glaser et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…14 chromosome abnormality in lymphoid cells of non-malignant origin, despite the presence of the EB viral genome (Jarvis et al, 1974;Zech et al, 1976), it is also not surprising that the cells of the NPC-derived lymphoblastoid lines lacked a consistent No. 14 chromosome abnormality (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been reported that a translocation from chromosome 8 to the long arm of chromosome 14 is observed in lymphomas, including Burkitt tumors (18)(19)(20). Whether or not the close association of EBV genome and EBNA with chromosome 14 is related to the mechanism of EBV-induced oncogenesis is deemed worthy of investigation.…”
Section: Methodsmentioning
confidence: 99%